2022
DOI: 10.1302/2046-3758.111.bjr-2021-0277.r1
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic liability between major depressive disorder and osteoarthritis

Abstract: Aims Deciphering the genetic relationships between major depressive disorder (MDD) and osteoarthritis (OA) may facilitate an understanding of their biological mechanisms, as well as inform more effective treatment regimens. We aim to investigate the mechanisms underlying relationships between MDD and OA in the context of common genetic variations. Methods Linkage disequilibrium score regression was used to test the genetic correlation between MDD and OA. Polygenic analysis was performed to estimate shared gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 93 publications
(126 reference statements)
1
23
0
Order By: Relevance
“…To achieve this, genetic variants are utilized as instrumental variables ( 34 ). The MR framework has been widely used in recent studies to explore relationships between related phenotypes ( 35 39 ). This study used the MR approach to test whether habitual tea intake exerts any causal influences on contracting SARS-CoV-2 and severe outcomes of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, genetic variants are utilized as instrumental variables ( 34 ). The MR framework has been widely used in recent studies to explore relationships between related phenotypes ( 35 39 ). This study used the MR approach to test whether habitual tea intake exerts any causal influences on contracting SARS-CoV-2 and severe outcomes of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…An awareness of the influence of these conditions on pain and physical wellbeing has increased among providers in recent years. [1][2][3] Mental and social health factors have been identified as potential contributors to persistent pain, dissatisfaction, and complication rates following total hip arthroplasty (THA) and total knee arthroplasty (TKA). [4][5][6][7][8] Previous investigations have suggested that up to 20% of patients are dissatisfied following primary TKA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an existing MR analysis demonstrated that high iron levels have a positive causality with gout but a negative causality with rheumatoid arthritis (RA) (17). In addition, the genetic causal association between major depressive disorder (MDD) and osteoarthritis (OA) has also been documented in a recent MR study (19). However, few studies have focused on the association between iron status and OP using MR analysis.…”
Section: Introductionmentioning
confidence: 99%